Solvothermal Synthesis of Reduced Graphene Oxide as Electrode Material for Supercapacitor Application - Thalji, Mohammad R.; Ali, Gomaa A. M.; Lee, Soon Poh; K. F., Chong (ISSR Publishing, 2019)
This work manifests the synthesis of reduced graphene oxide nanosheets through in situ solvothermal reduction of graphene oxide. The as-synthesized reduced graphene oxide nanosheets are utilized as a supercapacitor electrode. A series of structural and morphological investigations evince that graphene oxide can be successfully reduced through solvothermal strategy in absolute ethanol as solvent. Fourier transform infrared spectroscopy results showed that reduced graphene oxide displayed very low-intensity bands related to oxygenated functional groups, implying a high reduction degree. Besides that, it shows good electrochemical characteristics such as high specific capacitance of 183 F g-1 is obtained in 5 M KOH at 0.25 A g-1 and low internal and charges transfer resistances which are 430 and 64 mΩ, respectively. The findings confirm that graphene oxide can be reduced through solvothermal reduction strategy. Further, the as-prepared reduced graphene oxide nanosheets is a good candidate for supercapacitors application.